Peat soils sandsing influence to 137Cs reduce in plants - О. V. Kosarchuk; М. M. Lazarev; S. V. Polishchuk (Ядерна фізика та енергетика)
Uniqueness of radioecological situation in Ukraine is due to the presence of large areas of peat soils spread, for which abnormally high rates of radioactive cesium in plants are observed. Even in 30 years after the Chernobyl accident, agricultural products exceeding the requirements of AS-06 on peat soils with levels of contamination by 137Cs of about 37 kBk/m2 is produced. Developed and tested traditional antiradiation measures did not receive, due to some circumstances, the state support for the contaminated area. Therefore, we proposed alternative approaches to improve the radioecological situation on the contaminated peat soils.